(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
This study aimed to carry on a review on cognitive-behavioral theory (CBT) practice in schools, considering the period from 2015 to 2020. The Databases Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), and Electronic Periodicals in Psychology (PePSIC) were consulted, emplying the descriptors: "cognitive-behavioral theory", "school" and "teachers". Six studies were included in this review, analyzed in regard to five categories: interventions that used CBT techniques; actions focused on pedagogical practices; evaluations of intervention programs; and management of specific issues at school. The results depicted a scarcity and a predominance of intervention studies. Likewise, it was found that few studies mentioned CBT as an approach that supports practices that are developed at school. Nevertheless, it was noticed that many of these practices are based on the principles of CBT.